1998
DOI: 10.1055/s-2007-978936
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Leptin Levels in Newborns from Normal and Diabetic Mothers

Abstract: Leptin can be considered as a peripheral signal which informs the centers about the mass of energy stores. Studies done on the human adult population have demonstrated that degree of adiposity and insulin levels play a major role as determinants of leptin circulating levels. The aim of this study was to evaluate which factors may influence leptin levels at birth. We examined the role played by baby size and by the metabolic environment the fetus was exposed to during pregnancy. We considered 85 newborns from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 19 publications
(25 reference statements)
1
19
0
3
Order By: Relevance
“…The lowest levels were seen in the newborn infants of control mothers. Recent studies have shown similar findings [13, 14, 15]. The newborn infants of diabetic mothers were also found to be hyperinsulinemic as has been previously reported [15, 16].…”
Section: Discussionsupporting
confidence: 84%
“…The lowest levels were seen in the newborn infants of control mothers. Recent studies have shown similar findings [13, 14, 15]. The newborn infants of diabetic mothers were also found to be hyperinsulinemic as has been previously reported [15, 16].…”
Section: Discussionsupporting
confidence: 84%
“…Insulin-dependent diabetes (IDDM) mothers, although clinically well controlled, gave birth to newborns with significantly higher levels of leptin and insulin (26). Moderate increases in circulating leptin were recently reported to decrease considerably the expression of the gene for its synthesis in adipose tissue (14).…”
Section: Discussionmentioning
confidence: 99%
“…This concurs with the findings from several singleton studies, which report that plasma leptin concentrations at term are directly related to birth weight. A strong association between these two variables has also been reported in diabetic and IUGR infants, with a weak association for AGA fetuses (7,(31)(32)(33). Furthermore, the strong positive association between the percentage discordance in birth weight and the delta fetal plasma leptin concentrations suggests that intertwin differences in the growth discordant group may be partly related to disparity in fat mass accumulation or intrauterine fetal growth, and points toward a role for leptin as a regulator of fetal growth (33).…”
mentioning
confidence: 87%